Izpodbijanje sklepa o prenosu delnic v postopku izključitve manjšinskih delničarjev zaradi kršitve pravice do obveščenosti - Kerčmar, Sebastjan (Podjetje in delo, 2021)
The institute of squeeze-out of minority shareholders was enacted in Slovenian Companies Act by the adoption of the new Companies Act (ZGD-1) in 2006, whereas that institute was enacted in German legislation by the amendment to Aktiengesetz (AktG) as early as 2002. In adopting the new institute of squeeze-out, the Slovenian legislator took its inspiration from German provisions on squeeze-out of minority shareholders (327a-327f AktG). For a squeeze-out, a mere declaration of the principal shareholder is not enough - a transfer resolution must be adopted at the shareholders'' meeting. A challenge of the transfer resolution can be based on all grounds provided in Article 395 of the Slovenian Companies Act. However, according to Article 388 of the Companies Act, a challenge of the transfer resolution can not be based on the fact that the cash compensation, which has been offered by the principal shareholder, is not appropriate, has not been offered, or has not been offered correctly. The right to be informed is one of the fundamental shareholders'' rights that is exercised at the shareholders'' meeting. According to Slovenian legislation, the violation of the right to be informed is a separate ground for challenging a resolution of the shareholders'' meeting. A resolution of the shareholders'' meeting shall always be challengeable if the shareholders'' right to be informed is violated in connection with the adoption of the resolution. In the article, the authors address the question of whether the transfer resolution is challengeable because of incorrect, incomplete, or insufficient information in the shareholders'' meeting with respect to the determination, amount, or appropriateness of cash compensation.
Keywords: cash compensation; challenging the resolution of a shareholders' meeting; denarna odpravnina; glavni delničar; izključitev manjšinskih delničarjev; izpodbijanje skupščinskih sklepov; manjšinski delničarji; minority shareholders; pravica do obveščenosti; principal shareholder; registrska zapora; registry lock-up; right to be informed; sklep o prenosu delnic manjšinskih delničarjev na glavnega delničarja; squeeze-out of minority shareholders; transfer resolution